2024
DOI: 10.1128/mmbr.00094-23
|View full text |Cite
|
Sign up to set email alerts
|

Linking human milk oligosaccharide metabolism and early life gut microbiota: bifidobacteria and beyond

Cathy Lordan,
Aoife K. Roche,
Dianne Delsing
et al.

Abstract: SUMMARY Human milk oligosaccharides (HMOs) are complex, multi-functional glycans present in human breast milk. They represent an intricate mix of heterogeneous structures which reach the infant intestine in an intact form as they resist gastrointestinal digestion. Therefore, they confer a multitude of benefits, directly and/or indirectly, to the developing neonate. Certain bifidobacterial species, being among the earliest gut colonizers of breast-fed infants, have an adapted functional capacity to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 272 publications
0
1
0
Order By: Relevance
“…However, a negative association between P2 and B. breve was observed in this study. The inconsistencies may indicate that other factors beyond HMOs such as host-secreted glycans [55] or colonisation order of the Bifidobacterium species [56] have a greater influence on the infant gut microbiota. Furthermore, other commensal microbiota such as Bacteroides and Lactobacilli also possess the ability to degrade HMOs [57] and the competitive colonisation between these genera may also have an impact on our results.…”
Section: Association Of Other Hmo Patterns With Infant Gut Microbiotamentioning
confidence: 99%
“…However, a negative association between P2 and B. breve was observed in this study. The inconsistencies may indicate that other factors beyond HMOs such as host-secreted glycans [55] or colonisation order of the Bifidobacterium species [56] have a greater influence on the infant gut microbiota. Furthermore, other commensal microbiota such as Bacteroides and Lactobacilli also possess the ability to degrade HMOs [57] and the competitive colonisation between these genera may also have an impact on our results.…”
Section: Association Of Other Hmo Patterns With Infant Gut Microbiotamentioning
confidence: 99%
“…Apart from the role exerted by its own microbiota, which contributes to a healthy microbial diversification of the gut microbiota of newborns [ 65 , 66 ], the bioactive components of milk, especially oligosaccharides and whey proteins such as lactoferrin, lysozyme, and α-lactalbumin, have been shown to play a crucial role in shaping the gut microbiota from birth to adulthood [ 67 , 68 ]. Indeed, studies have reported the role of human and cow’s milk constituents in promoting the growth of beneficial probiotic bacteria, including B. infantis , B. Pennsylvanicus , B. longum , B. bifidum , and B. breve [ 69 , 70 , 71 , 72 ].…”
Section: Introductionmentioning
confidence: 99%